Angle distortion theorems for starlike and spirallike functions with respect to a boundary point - Mark Elin; David Shoikhet (International Journal of Mathematics and Mathematical Sciences)
We exhibit angle bounds for starlike and spirallike functions with respect to a boundary point. As an application, we obtain a covering theorem for functions convex in one direction.